2016
DOI: 10.1021/acs.energyfuels.5b02512
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Engine Age on Morphology and Chemistry of Diesel Soot Extracted from Crankcase Oil

Abstract: In this study, the role of engine age on the structure and chemistry of crankcase soot was studied using X-ray diffraction, high-resolution transmission electron microscopy, energy-dispersive spectroscopy, and Raman spectroscopy. Results indicate that the basic structure of the carbonaceous species remains the same in all cases and is composed of turbostratic carbon. However, there are some very subtle changes in the structure of the soot as the age of the engine increases. Older engines have a greater proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Some of the particles further exhibited crystalline regions (see Figure 7), which were found to promote wear in engines [62]. Such behaviour was observed by Sharma et al [63] for diesel engines particularly with higher engine age. Several studies suggested that the crystalline structures could stem from wear elements and oil additives [10,14,40].…”
Section: Transmission Electron Microscopysupporting
confidence: 66%
“…Some of the particles further exhibited crystalline regions (see Figure 7), which were found to promote wear in engines [62]. Such behaviour was observed by Sharma et al [63] for diesel engines particularly with higher engine age. Several studies suggested that the crystalline structures could stem from wear elements and oil additives [10,14,40].…”
Section: Transmission Electron Microscopysupporting
confidence: 66%
“…Sharma et al [58] observed such behaviour in diesel engines particularly with increasing engine age. However, here crystalline regions are only observed in the GTDI samples, suggesting a difference between the soot types.…”
Section: Hrtemmentioning
confidence: 86%
“…Raman spectroscopy can be used to characterize crystallite and molecular structures of soot particles. 33 Different structural characteristics of PM can be distinguished 53 according to the fitted curves from the Raman spectrum (see Figure 1) with different peaks explained in Table 2. It is worth mentioning that the Raman spectra recorded at λ = 633 nm also exhibited second order spectra above 2000 cm −1 Raman shift, but only the first order spectra were considered for further analysis.…”
Section: Environmental Science and Technologymentioning
confidence: 99%